THE EFFECT OF ‘LEARN ENGLISH WITH TV SERIES’ IN INCREASING VOCABULARY SIZE FOR THE THIRD GRADE STUDENTS AT SMAN 2 MAROS - Andi Asmawati; Sri Widyastuti; Suhrah (elstic : english language linguistics culture, 2022)
This study aims to determine the students’ vocabulary size taught by using Learn English with TV Series as a learning medium. The research method used in this research was pre-experimental with a pre-test and post-test group design. The sample was the class XII MIPA at SMAN 2 Maros consisting of 30 students selected using probability sampling with a simple random sampling technique. The instrument used were a multiple-choice, true-false item, matching test, and vocabulary level test. The collected data was then analyzed using SPSS. The result indicated that the average score of the post-test (90.40) was higher than the pre-test (49.97). It was supported by the one-sample T-Test where Sig. (2-tailed) 0.000 < 0.05, which had a good and significant effect on students. The result of the vocabulary level test also indicated that the students at level 2000. Therefore, the students’ vocabulary size was increased using Learn English with TV Series YouTube Channel at SMAN 2 Maros.